INVENTARISASI SERANGGA HAMA PADA TANAMAN KUBIS DI KELURAHAN KUMELEMBUAY KOTA TOMOHON - Arthur Roring; Elisabet R.M. Meray; Max Ratulangi; M.F. Dien (COCOS, 2017)
ABSTRACT The study aims to determine the types of insect pests on cabbage in the village Kumelembuay. Tomohon. The experiment was conducted in an area per plant cabbage in the Village Kumelembuay, Tomohon, then continued at the Laboratory of Entomology and Plant Pests UNSRAT Faculty of Agriculture. The study lasted four months, namely since january to april 2015. The study used survey method to the location in the Village Kumelembuay cabbage, Tomohon. Sampling was conducted on cabbage planting area. Land used in this study is the land that has been planted with cabbage crops by farmers. Sampling was done by using insect nets and making direct use of the hands. Sampling was conducted using an insect net sweep with five double swing on the surface of cabbage; while the decision is directly determined each block as many as 25 plants and then take larva, nymph imago insect mupun been recorded. Insects obtained collected in the bottle collection that already contains 70% alcohol. Sampling was conducted four times: two times on young plants and twice in plants that make up the crop. Insects insect (imago) is sized caught using insect nets collected dry, while for small insects or larvae and nymphs collected in a bottle of alcohol 70%. Insects found are split according to its kind later in the collection (adult insect collection of dry, whereas insects pradewasa (larvae and nymphs collected wet). The insects had been identified to determine its type. Identification carried out in the Laboratory of Entomology and Pest Plants, Faculty of Agriculture Unsrat. Small insects found preserved and included in the collection bottle containing 70% alcohol. Large insects preserved in a dry ie included in the collection box and then insects labeled. Insect identification is done using a microscope and identification be to a degree relatives by using insect identification keys. Identification conducted at the Laboratory of Entomology and Plant Pests Faculty of Agriculture of UNSRAT. The data obtained were then analyzed using descriptive and do tabulation and calculated the average population of insect pests on cabbage. 4 The results showed that the thirteen species of insects found on cabbage plants in the village Kumelembuay, four of which are pests on cabbage. The identification results show that different types of insect pests that attack cabbage plants in the village Kumelembuay are: (1) Family Pyralidae Order Lepidoptera alleged Crocidolomia pavonana (2) Family Plutellidae Order Lepidoptera suspected as Plutella xylostella (3) Family Noctuidae Order Lepidoptera that Chrysodeixix chalcites alleged funding of the Order Homoptera Aphididae Family alleged Aphis sp. The average population of insect pests on famli Pyralidae dijumpaia highest reached 65.93 tails, then tails Family Aphididae 61.56, 30.18 Plutellidae tail and tail Family Noctuidae 0.75. Besides insect pests also found other types of insects insect berifat well as natural enemies as well as newcomers. Types of predatory insects found are Coccinelidae Family, Family Labillulidae, Amili Sphecidae, Family asilidae. Family Ichneumonidae parasitoid insects are and Tachinididae, while insect migrants are Scarabidae Family and Family Erebidae. Key word : Cabbage, insect pest